Phellinus linteus Grown on Germinated Brown Rice Increases Cetuximab Sensitivity of KRAS-Mutated Colon Cancer - Park, Hye-Jin (Int J Mol Sci, 2017)
Colon cancer is one of the most common types of cancer, and it has recently become a leading cause of death worldwide. Among colon cancers, the v-ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS)-mutated form is notorious for its non-druggable features. Cetuximab, a monoclonal antibody that binds to the epidermal growth factor receptor, has been introduced as an antitumor therapy; however, secondary resistance and side effects significantly limit its effective use in these cancers. In this study, we prepared Phellinuslinteus on germinated brown rice (PBR) extracts to increase the sensitivity of KRAS-mutated colon cancers to cetuximab. The combined treatment of PBR extract and cetuximab suppressed SW480 cell viability/proliferation, with the cells exhibiting altered cellular morphology and clonogenic potential. AnnexinV–fluorescein isothiocyanate/propidium iodide–stained flow cytometry and Western blotting were performed, and PBR extract combined with cetuximab treatment increased apoptosis of the SW480 cells and suppressed their KRAS protein expression. The potential of PBR as a synergistic anticancer agent was further investigated in a tumor-xenografted mouse model. Tumor growth was significantly suppressed with PBR extract and cetuximab co-treatment. In conclusion, PBR increased the sensitivity of KRAS-mutated colon cancer cells to cetuximab, which indicates the potential use of PBR as a medical food against colon cancer.